Results of reconstruction of a Deel artifact unearthed from the burial of Balar’s Khad, Ikh Nart - Chuluun, Altantsetseg; Bayanzul, Munkhtsetseg; Palamkhan, Bolormaa (Mongolian Journal of Arts and Culture, 2024)
This paper presents findings from the research conducted under the collaborative project “A study of the documentary evidence to reveal the values and cultural mentality of the Mongols during the Mongol Empire” by the Research Institute of Arts and Culture, Mongolian National University of Arts and Culture (MNUAC) and the Institute of Archaeology, Mongolian Academy of Sciences. The study focuses on the design and pattern reconstruction of a Deel artifact dating back to the Mongol Empire and Yuan Dynasty. The research was carried out in the laboratory of the Institute of Archaeology, employing methods such as observation, comparison, measurement, and graphic calculations. Reconstruction techniques were applied, alongside photogrammetry and digital processing, to recreate the silk patterns. The analysis and reconstruction revealed that the Deel garment featured continuous cuts along the waistline and shoulder line, a snug fit around the waist, loose underarm areas for comfort, and long, narrow sleeves. The collar and front were diagonally overlapped with a double-layered flap, and the garment included double-pleated slits at the hips. It was insulated with fine silk fibers for warmth, indicating it was a classic design for men’s seasonal wear (warm-weather deel) from the Mongol Empire period. It was also determined that the garment was covered in silk fabric decorated with gold threads patterns woven, each pattern depicting a recumbent antelope with its head turning to its rear under a full moon. Их Нартын Баларын хадны оршуулгаас олдсон дээлийг сэргээн бүтээсэн судалгааны үр дүн Хураангуй: Энэхүү өгүүлэлд СУИС-ийн Соёл, урлаг судлалын хүрээлэн, ШУА-ийн Археологийн хүрээлэнгийн хамтарсан “Монголын эзэнт гүрний үеийн монголчуудын үнэт зүйлсийг баримтаар мөшгөх судалгаа” төслийн хүрээнд Монголын эзэнт гүрэн, Юань гүрний үеийн дээлийн олдвор дурсгалд хийж буй судалгааны ажлын нэг хэсэг болох дээлийн зохион бүтээлт болон торгоны хээг нэхэн сэргээсэн ажлаас танилцуулав. Судалгааг Археологийн хүрээлэнгийн лабораторид хийж гүйцэтгэсэн ба судалгаандаа ажиглалт, харьцуулалт, хэмжилт, график тооцооны арга зэрэгт үндэслэн археологийн олдвор дурсгалыг нэхэн сэргээх (реконструкц) аргыг хэрэглэснээс гадна фотограмметр, дижитал боловсруулалтын аргаар торгоны хээг нэхэн сэргээв. Ийнхүү судалж, зохион бүтээлтийн зураглал, дээлийн өнгө торгоны хээг нэхэн сэргээснээр уг дээл нь бүсэлхийн шугам, мөрний шугамаар үргэлж эсгэлттэй, бүсэлхийгээр бариу, суга өргөн чөлөөтэй, ханцуйн үзүүр урт, нарийн, зах, энгэр нь ташуу зөрсөн, лав давхар зөрлөг энгэртэй, ташаандаа хоёр давхар нугалаа бүхий хагалаа оноотой, торгон ширхэглэг зулж дулаалсан байгаа нь Монголын эзэнт гүрний үеийн эрэгтэйчүүдийн сэрүүн улирлын (дулаан дээл) сонгодог загвартай дээл болохыг тодорхойлов. Мөн, уг дээлийг бодь гөрөөсний дүрслэл бүхий алтан утаст хээтэй торгоор өнгөлсөн болохыг тогтоов. Түлхүүр үгс: археологийн олдвор, хувцас, сэргээн бүтээх